Mineralocorticoid receptor antagonist use following heart failure hospitalization. (8th February 2020) - Duran, Jason M.; Gad, Shady; Brann, Alison; Greenberg, Barry
Abstract: Aims: Patients hospitalized for heart failure (HF) are at increased risk for events post‐discharge. Mineralocorticoid receptor antagonists (MRAs) improve the clinical course of patients with HF with reduced ejection fraction. We assessed MRA use in high‐risk patients following an HF hospitalization to determine rate of MRA prescription, likelihood of drug continuation post‐discharge, reasons for discontinuation, and association between MRA maintenance and outcomes. Methods and results: Patients admitted to our hospital system between 2011 and 2013 were identified retrospectively through automated search of electronic medical records for appropriate ICD 9 and 10 codes. Patients with left ventricular ejection fraction <40%, New York Heart Association class III–IV symptoms, >1 year of follow‐up and no contraindication to MRA use were included. Of 271 patients meeting inclusion criteria, 105 (38.7%) were prescribed an MRA on discharge from index admission. Over a median follow‐up of 3.12 ± 0.09 years, 70 (66.7%) continued MRA therapy, while 35 (33.3%) discontinued MRA therapy. Hyperkalemia, which occurred in 43 of the 105 patients (40.1%), was the most frequent cause of MRA discontinuation. Patients who maintained MRA therapy had significantly less all‐cause, cardiovascular, and HF hospitalizations and significantly better survival compared with those who discontinued drug. Conclusions: A minority of HF with reduced ejection fraction patients who were eligible for an MRA received them following HF hospitalization and nearly a third of them discontinued drug. Patients who discontinued an MRA were more likely to be hospitalized or die during follow‐up. These findings indicate a need for better strategies to increase MRA prescription and maintain therapy following a hospitalization for HF.